Junior High School Students’ Ability of Chinese Initial and Finals Pronounciation in Speaking - Muthmainnna, Risna; Azizah, Laelah; Junaeny, Arini (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2023)
Based on preliminary observations at Tunas Bangsa Makassar Junior High School, pronunciation in Mandarin is quite difficult because pronunciation in Mandarin is different from Indonesian. In this regard, the purpose of this research is to determine the ability to pronounce shēngmǔ and yùnmǔ in Mandarin. This research is quantitative descriptive. The research subjects were students of class VII Tunas Bangsa Makassar Junior High School with a total of 9 students. The techniques used to collect research data are observation techniques and test techniques. The test instrument was used to determine the ability to pronounce shēngmǔ and yùnmǔ in Mandarin for class VII students of Tunas Bangsa Makassar Junior High School. The results showed that the students' average pronunciation ability was 44 with a standard deviation of 10.25 and was at intervals of 46-55. Thus it can be concluded that the level of ability to pronounce shēngmǔ and yùnmǔ in Mandarin for class VII students of Tunas Bangsa Makassar Junior High School is at moderate criteria.